Role of organic carbon and nitrogen of mineral waters in their immunomodulating effects at female rats - Popovych, Igor; Mysula, Igor; Popovych, Andriy; Mysula, Yuriy; Sydliaruk, Nataliya; Bilas, Volodymyra; Zukow, Walery (Journal of Education, Health and Sport, 2021)
Background. Drinking mineral water is one of the ethnopharmacologic factors. Organic substances, despite their presence in all drinking mineral waters, are still considered to be active only in the water of Naftussya type (which, due to mineralization less than 1 g/L, are not formally mineral), whereas the physiological activity of true mineral waters (which mineralization is greater than 1-2 g/L) are associated with electrolytes and trace elements. Previously, we identified the role of organic carbon and nitrogen of mineral waters in their effects on certain metabolic and neuro-endocrine parameters. The purpose of this study is to clarify the role of organic substances of same mineral waters in their effects on immunity parameters. Material and methods. Experiment was performed on 48 healthy female Wistar rats 240-290 g divided into 5 groups. Animals of the first group for 6 days administered a single tap water through the tube at a dose of 1,5 mL/100 g of body mass. In the second group we administered the water Naftussya from the Truskavets’ layer (Galychyna, Ukraine), in the third group the water Sophiya of the Truskavets’ field. The rats of the fourth group received the native water from the Hertsa (Bucovyna, Ukraine) field, and the last group received its artificial salt analogue. The day after the completion of the drinking course in all rats immunne parameters were registered. Results. On the basis of the correlation analysis with step-by-step exclusion, 9 immune parameters (Endotheliocytes of Thymus, Spleen Mass Index, Entropy of Splenocytogram, Natural Killers, B- and 0-Lymphocytes, Rod-shaped Neutrophils, Phagocytic Index and Microbian Count of Monocytes of Blood) are included in the regressive model for organic nitrogen (R=0,818) and 6 parameters (Endotheliocytes of Thymus, Fibroblastes and Reticulocytes of Spleen, Pan-Lymphocytes, Microbian Count of Neutrophils and Phagocytic Index of Monocytes of Blood) for organic carbon (R=0,690). Together, the organic components of the chemical composition of loading fluids determine their effect on the immune parameters by 77%. Conclusion. Organic substances of mineral waters play an essential role in their effects on the immune parameters of female rats.